Adjunctive High-Definition Transcranial Direct Current Stimulation in Brain Glutamate-Glutamine and γ-Aminobutyric Acid, Withdrawal and Craving During Early Abstinence Among Patients With Opioid Use Disorder on Buprenorphine-Naloxone: A Proton Magnetic Resonance Spectroscopy–Based Pilot Study. Issue 2 (3rd June 2022) - Kumar, Aravind S.; Khanra, Sourav; Goyal, Nishant; Dharani, Ramamoorthy; Roy, Chandramouli
Abstract : Objective: Our study aimed to (1) examine the effect of adjunctive high-definition transcranial direct current stimulation (HD-tDCS) in craving and withdrawal among patients with opioid use disorder on buprenorphine-naloxone, and (2) examine effect of HD-tDCS changes in glutamate-glutamine and γ-aminobutyric acid (GABA) at the left dorsolateral prefrontal cortex (DLPFC) among patients with opioid use disorder on buprenorphine-naloxone. Methods: This was a pilot randomized double-blind, sham-controlled parallel-group study. A total of 28 patients on buprenorphine-naloxone (6/1.5 mg/d) were randomly allocated into 2 groups for active and sham HD-tDCS stimulation. High-definition transcranial direct current stimulation was administered twice daily for consecutive 5 days, from days 2 to 6. The Clinical Opiate Withdrawal Scale (COWS), the Desire for Drug Questionnaire (DDQ), the Obsessive-Compulsive Drug Use Scale (OCDUS), and glutamate-glutamine and GABA at DLPFC via proton magnetic resonance spectroscopy were measured at baseline and on day 7. Results: Both active and sham groups had comparable changes in DDQ, OCDUS (except 2 subcomponents), COWS, and glutamate-glutamine and GABA at DLPFC. In the active HD-tDCS group, statistically significant reductions were observed in DDQ, OCDUS, and COWS but not in glutamate-glutamine and GABA. Conclusions: The adjunctive active HD-tDCS group showed comparable changes in craving and withdrawal, and glutamate-glutamine and GABA at DLPFC compared with sham HD-tDCS. Craving and withdrawal but not glutamate-glutamine and GABA at DLPFC decreased significantly with adjunctive HD-tDCS. Future studies with larger sample size and online assessment of glutamate-glutamine and GABA would enhance our knowledge.